DETECTION OF Staphylococcus aureus FROM LOCAL AND IMPORTED CHICKEN IN DUHOK PROVINCE/KURDISTAN REGION OF IRAQ USING CONVENTIONAL AND MOLECULAR METHODS - Rezheen F. Abdulrahman (Basrah Journal of Veterinary Research)
This study aimed to detect Staphylococcus aureus in local fresh whole chicken andfrozen imported chicken using conventional and PCR assay by targeting specific S. aureusthermonuclease gene (nuc). A total of 200 whole chicken carcasses were examined andsamples include 100 of local chickens from the Duhok chicken abattoir and 100 of importedchicken from supermarkets in Duhok city. The samples were cultured on mannitol salt agarand the confirmation is done by colony morphology, Gram stain, biochemical test includingcatalase test and coagulase test. The results showed that 28 (28%) of 100 local chicken and80 (80%) of 100 imported frozen chicken carcasses were found to be positive with S. aureususing conventional methods. Amplification of nuc gene specific for S. aureus is used toconfirm the isolates of S. aureus. The results showed that only 18 of 22 coagulase positiveisolates from local chicken and 57 of 68 coagulase positive isolates from imported chickenwere confirmed as S. aureus. The results indicate that PCR assay seem to be more specific fordetection of S. aureus in food sample and appear to be more reliable than conventionalmethods for assessing bacteriological safety of food. These results showed high prevalence ofS. aureus in imported chicken than in local chicken meat and thus may happen as a result ofprocessing and storage conditions.